Perspectivas do desenvolvimento e utilização de ambientes virtuais em game engine para ergonomia - Paravizo, Esdras (Universidade Federal de São Carlos, 2021)
As the popularization of innovative digital technologies consolidates, new possibilities emerge for their use in diverse contexts, including in research and teaching situations. This is the context of Game Engines (GEs) - digital tools commonly used for the development of electronic games, but that can be mobilized to create virtual environments with various objectives. This paper seeks to understand how virtual environments created in game engines can contribute to the field of ergonomics as a tool for simulation and teaching. To do so, four studies were developed and articulated: the first one deepened the discussion about the VE in GE for the simulation and analysis of work situations, indicating the potentials and limitations of this approach. The second presented an initial attempt to systematically investigate the use of VE in GE in teaching contexts by structuring a comparative experimental study. Based on the consolidated experience with these articles and the identification of a gap in the literature regarding the standardization of the development of VE in GE, the third study was designed to contribute with a framework to systematize the creation of VEs in GEs. The last study validates this framework by implementing it to develop a VE for teaching ergonomics that was validated in pilot testing and in interviews with experts. Thus, it is understood that the present work contributes to a better understanding of the potential of using VEs in GE for ergonomics, both in work simulation and analysis contexts, and in teaching contexts. The results achieved here contribute both to the theoretical field of simulation in ergonomics, and to its practice and teaching, which is particularly relevant in a context in which Brazil and the world seek new ways of teaching.
Perspectives on the development and use of game engine-based virtual environments for ergonomics
Keywords: Ergonomia; Ensino; Projeto; Game engine; Framework; Ergonomics; Education; Design; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO